Efficacy and exploratory biomarker analysis of entinostat plus exemestane in advanced or recurrent breast cancer: phase II randomized controlled trial. (17th November 2022) - Iwata, Hiroji; Nakamura, Rikiya; Masuda, Norikazu; Yamashita, Toshinari; Yamamoto, Yutaka; Kobayashi, Kokoro; Tsurutani, Junji; Iwasa, Tsutomu; Yonemori, Kan; Tamura, Kenji; Aruga, Tomoyuki; Tokunaga, Eriko; et al.
Abstract: Background: We aimed to confirm the efficacy and safety of the oral histone deacetylase inhibitor entinostat in Japanese patients with hormone receptor-positive advanced/recurrent breast cancer and to explore potential biomarkers. Methods: This phase II, double-blind, randomized, placebo-controlled trial (ClinicalTrials.gov ; NCT03291886) was conducted at 28 Japanese sites (September 2017–July 2020; interim analysis cutoff: April 2019). Patients with progression/relapse following non-steroidal aromatase inhibitors were randomized 1:1 to entinostat (5 mg/week) or placebo, plus exemestane (25 mg/day). Primary endpoint was progression-free survival; secondary endpoints included overall survival and safety. Exploratory biomarker outcomes included lysine acetylation, immune cell profiles, estrogen receptor 1 mutations and plasma chemokines. Results: Of 133 randomized patients, 131 (65 entinostat, 66 placebo) who received study drug were analyzed. Median (95% confidence interval) progression-free survival was 5.8 (3.2–7.8) months for entinostat and 3.3 (3.1–5.8) months for placebo (hazard ratio [95% confidence interval]: 0.75 [0.50 − 1.14]; P  = 0.189). Median overall survival was not reached in either group. Entinostat tended to prolong progression-free survival in patients aged ≥65 years, not endocrine resistant, or with estrogen receptor 1 Y537S mutation. Candidate biomarkers of efficacy (progression-free survival) included lysine acetylation in CD3+ cells, plasma interferon gamma-induced protein 10, dendritic cell CD86 expression, and CD4+ cell expression of human leukocyte antigen-DR and inducible T-cell co-stimulator. Safety was similar to non-Japanese populations; however, seven entinostat-treated patients (10.8%) had reversible lung injury. Conclusions: In Japanese patients, the safety of entinostat plus exemestane was acceptable and progression-free survival was prolonged, although not significantly. Exploratory analyses identified potential biomarkers, including lysine acetylation, of efficacy. Abstract : The European and American uterine cervical cancer guidelines recommend delivering > 85 Gy to the CTVHR D90, the Japanese guidelines do not recommend delivering such a high dose. Subsequently, while late toxicities in the Japanese schedule are milder than those in the Western schedule, local control is also lower. In this article, we hope to raise a discussion in our community about modifying our guidelines to recommend a higher dose, at least for patients with poor response.